2013
DOI: 10.1111/tbj.12097
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Induced Protein with Tetratricopeptide Repeats 1 (IFIT1) as a Prognostic Marker for Local Control in T1-2 N0 Breast Cancer Treated with Breast-Conserving Surgery and Radiation Therapy (BCS + RT)

Abstract: Interferon-induced protein with tetratricopeptide repeats 1 (IFIT1) expression, involved in the regulation of translation, has been implicated to mediate resistance to chemotherapy and radiation in cancer cells in vitro. The purpose of this study was to evaluate the prognostic significance of IFIT1 protein expression in patients with breast cancer treated with Breast-Conserving Surgery and Radiation Therapy (BCS + RT). A tissue microarray was constructed with specimens from 282 women with node-negative, early-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
0
12
1
Order By: Relevance
“…IFIT1-positive cells were more frequent after infection (Figures 5C and 5F), but highly upregulated in SIV, in cells localized in the perivascular domain (Figure 5I). This finding is contrasting with other findings in the literature, showing that IFIT1 is upregulated in HIV+ elite controllers(Krishnan et al 2014), or in cancer patients, where high levels of IFIT1 correlate with improvement following treatment(Danish et al 2013). On the other hand, it has been shown that a high expression of IFIT1 in areas of the brain is a marker of aberrant IFN response in aging(Baruch et al 2014).…”
Section: Resultscontrasting
confidence: 99%
“…IFIT1-positive cells were more frequent after infection (Figures 5C and 5F), but highly upregulated in SIV, in cells localized in the perivascular domain (Figure 5I). This finding is contrasting with other findings in the literature, showing that IFIT1 is upregulated in HIV+ elite controllers(Krishnan et al 2014), or in cancer patients, where high levels of IFIT1 correlate with improvement following treatment(Danish et al 2013). On the other hand, it has been shown that a high expression of IFIT1 in areas of the brain is a marker of aberrant IFN response in aging(Baruch et al 2014).…”
Section: Resultscontrasting
confidence: 99%
“…The antiviral functions of human IFIT proteins have been extensively demonstrated in many research studies Sen, 2011, 2015;Diamond and Farzan, 2013). Recent studies have implicated IFIT proteins as prognostic markers to determine the clinical outcome of many cancers, such as glioblastoma, hepatocellular carcinoma, breast cancer and pancreatic cancer (Danish et al, 2013;Zhang et al, 2016;Yang et al, 2017;Zhao et al, 2017). During the past several years, we explored the biological and clinical functions of IFIT proteins in oral squamous cell carcinoma (OSCC) (Blot et al, 1988;Lai et al, 2008Lai et al, , 2013Pidugu et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%
“…Pei et al reported the role of IFIT1 in the limitation of hepatitis B virus replication, while Danish et al introduced IFIT1 as a prognostic marker for local control in T1-2 N0 breast cancer treated with breast-conserving surgery and radiation therapy. 25,26 Like the other central DEGs, IFIT1 is connected to most of the biological processes (see Figure 4).…”
Section: Discussionmentioning
confidence: 99%